2004
DOI: 10.1038/sj.onc.1207493
|View full text |Cite
|
Sign up to set email alerts
|

PIN1 overexpression and β-catenin gene mutations are distinct oncogenic events in human hepatocellular carcinoma

Abstract: The peptidyl-proplyl-isomerase, PIN1, upregulates b-catenin by inhibiting its interaction with APC. b-catenin accumulation occurs in about 70% of hepatocellular carcinoma (HCC), of which only 20% are due to b-catenin mutations. The role of PIN1 in b-catenin upregulation in HCC was investigated. PIN1 was shown to be overexpressed in more than 50% of HCC. All cases with PIN1 overexpression also showed b-catenin accumulation, with 68% of cases showing concomitant b-catenin and cyclin D1 accumulation. PIN1 was sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 22 publications
6
88
3
Order By: Relevance
“…For example, PIN1 (a prolyl cis/ trans isomerase), which has been shown to inhibit bcatenin/APC interaction (Ryo et al, 2001), is upregulated with subsequent accumulation of b-catenin in more than 50% of all HCCs (Pang et al, 2004). Ezrinradixin-moesin binding phosphoprotein 50 (EBP50), on the other hand, elevates b-catenin/TCF-mediated transcription (Shibata et al, 2003).…”
Section: Signaling Pathways and Their Dysregulationmentioning
confidence: 99%
“…For example, PIN1 (a prolyl cis/ trans isomerase), which has been shown to inhibit bcatenin/APC interaction (Ryo et al, 2001), is upregulated with subsequent accumulation of b-catenin in more than 50% of all HCCs (Pang et al, 2004). Ezrinradixin-moesin binding phosphoprotein 50 (EBP50), on the other hand, elevates b-catenin/TCF-mediated transcription (Shibata et al, 2003).…”
Section: Signaling Pathways and Their Dysregulationmentioning
confidence: 99%
“…In addition, Pin1 has been demonstrated to bind directly to phosphorylated ß-catenin at pT246P motif in vitro and in vivo and block the interaction between ß-catenin and APC (15,34). Moreover, Pin1-ß-catenin signaling has been shown to regulate cyclin D1 expression in human breast and liver cancers when Pin1 was overexpressed (16)(17)(18)(19)(20). These studies suggested a mechanism that overexpression of Pin1 contributes to the ß-catenin accumulation and increases the nuclear fraction of ß-catenin by preventing its interaction with APC in tumors that consequently elevates the cyclin D1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Pin1 has been shown to interact with a number of cancer-related phosphoproteins, which suggested Pin1 might link signal transduction to pathogenesis of cancer (1,15,16). Moreover, Pin1 overexpression in several human cancers including breast and prostate and liver cancers strongly suggested that Pin1 might play a role in tumorigenesis (16)(17)(18)(19). Given the role of Pin1 in cell growth control and tumorigenesis, Pin1 could represent a new anti-cancer target.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variations are thought to influence the risk of developing HCC (Edmondson, Henderson et al, 1976;Cha and Dematteo, 2005), particularly those that involve the activation of cellular oncogenes or the inactivation of tumor suppressor genes in various signaling pathways (e.g., mutation of beta-catenin-related Wnt/beta-catenin signals (Pang, Yuen et al, 2004) and overexpression of Ras signaling (Mitin, Rossman et al, 2005)). Also, single nucleotide polymorphsims (SNPs) of many famous genes, such as p53 (Kirk, Lesi et al, 2005), HDAC10 (Park, Kim et al, 2007) and MMP2 (Wu, Zhang et al, 2008), have been significantly associated with HCC.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, various growth factors were found to enhance HCC cell proliferation, as well as tu-mor invasion and metastasis, via the activation of the Ras/Raf-1/extracellular signal-regulated kinase (ERK) pathway (Nonomura, Ohta et al, 1987;Pang, Yuen et al, 2004;Tsuboi, Ichida et al, 2004). Also, overexpression of Ras genes is common in human HCC tissue.…”
Section: Introductionmentioning
confidence: 99%